DETERMINAN PEMILIHAN KANTOR AKUNTAN PUBLIK (KAP) - Febby; Sugi Suhartono (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2020)
Abstract In the process of maximizing the value of the company, a conflict of interest between the manager and the shareholders often arises, which is often called an agency problem. This happens because managers prioritize the opposite interests, ownership does not like the personal interests of managers because what managers do will add costs to the company so that it will cause a decrease in corporate profits. Therefore, companies need a corporate monitoring function through external auditors that are used by company managers to reduce agency problems that arise in the company and reduce fraud in the presentation of the company's financial statements. Therefore, this study discusses the factors that can influence the decisions of public accounting firms such as institutional share ownership, managerial stock ownership, largest shareholding, company size, independent commissioners and leverage. The sample in this study consisted of 135 manufacturing companies. Sampling was done by purposive sampling method. The analytical method used is logistic regression analysis using SPSS 20. The conclusion from the results of the analysis in this study is that the largest shareholding has a positive interest in the selection of a public accounting firm. Keywords: Selection of Public Accounting Firm, Independent Commissioner, Institutional Ownership, Managerial Ownership, Largest Share Ownership, Company Size, Leverage. References: Alfian, N., & Suryansyah, A. (2017).